Human Rhinovirus/Enterovirus in Pediatric Acute Respiratory Distress Syndrome - Smith, Michele E.; Wilson, Patrick T. (Journal of Pediatric Intensive Care, 2020)
The role of human rhinovirus/enterovirus (HRV/HEV) in severe lower respiratory tract infections remains unclear. We characterized the respiratory status of children admitted to a large academic pediatric intensive care unit (PICU) who tested positive for only HRV/HEV. One hundred and fifty-five children met inclusion criteria with 62% requiring positive pressure respiratory support of 5 cm of water pressure or more within the first 24 hours of admission. Among them, 34% had SaO2 to FiO2 ratios of 264 or less with 22 patients (14%) meeting criteria for pediatric acute respiratory distress syndrome. HRV/HEV is associated with significant respiratory disease in children admitted to the PICU.
Keywords: rhinovirus; enterovirus; pediatric intensive care units; pediatric acute respiratory distress syndrome